Pathological factors involved in local failure in squamous cell carcinoma of the oral cavity: retrospective study and proposal of a new clinical classification. Issue 2 (February 2019) - Toratani, S.; Ogawa, I.; Sasahara, H.; Yoshioka, Y.; Kanda, T.; Tani, R.; Okamoto, T.
Abstract: The control of local failure (LF) is essential to improve outcomes in patients with squamous cell carcinoma of the oral cavity (OSCC). In this study, LF of OSCC was classified into three clinical types: deep recurrence (type 1R), adjacent superficial recurrence (type 2R), and distant primary tumour (type 3R). LF was analyzed after surgical resection of OSCC to determine the validity and usefulness of this classification system. Of 257 patients with OSCC, 58 experienced LF; 21 had type 1R, 23 had type 2R, and 20 had type 3R. Clinical factors influencing LF were analyzed by log-rank test and Cox test. Type 1R was significantly related to the TN classification, resection margin status, and invasive pattern. Type 2R was strongly associated with the grade of epithelial dysplasia at the surgical margins. Type 1R rarely developed more than 1 year after surgery, whereas type 2R did not develop within 2 years. Type 1R may be caused by residual cancer cells in the deep margins, and type 2R by precancerous cells remaining in the marginal epithelium and gradually becoming invasive cancer. Type 3R may be considered an independent tumour. The newly proposed clinical classification is convenient and roughly reflects the causes and mechanisms of relapse.